Частный дом в г. Феникс, штат Аризона, США - Spencer, Brian A. (проект байкал, 2005)
Brian Spencer, AIA / IAA is a registered architect with 32 years of experience. He has worked domestically throughout the United States, as well as internationally in Europe and the Pacific Rim…Spencer is one of only five American architects elected a foreign member of the Russian Academy of Architecture & Construction Sciences. He is both Professor and Academician in the International Academy of Architecture in Sofia, Bulgaria and serves on its' Academic Council.And he was also elected Honorary Visiting Professor at the Politechnika Gdanska in Gdansk, Poland. Brian is an adjunct faculty member of the Frank Lloyd Wright School of Architecture and serves on the Board of Directors of the Frank Lloyd Wright Wisconsin Heritage Tourism Program.